Perilaku Balok Baja I Non Prismastis (Tapered Beam) - Titin Sundar; Agoes Soehardjono; Wisnumurti Wisnumurti (Rekayasa Sipil, 2017)
The use of bending structure components becomes economical if the cross section of the beam follows the moment-diagram form. In this research is a simple beam with concentrated load in the middle of the span, so that the height of the beam is maximum in the middle of span, too. The research purpose is to obtain the bending capacity and to know the buckling behavior for optimum design. The results are compared with theoretical calculations, and ANSYS validation. Concluded of this research that the larger the tapered constant, the greater the bending capacity. The smaller the tapered angle the greater bending capacity. For the same tapered angle with higher h max, the bending capacity is also greater. The collapse occurring on this beam is the lateral torsional buckling.